Intersectional configuration of infant mortality due to malnutrition in Colombia: a mini-review - Taborda Restrepo, Paula A. (Frontiers in Public Health, 2024)
This mini review delves into the complex issue of mortality linked to malnutrition, highlighting its multifaceted nature beyond just biomedical factors, presenting it as an intricate intersectional phenomenon. Method: The mini-review methodology involved a systematic literature search across databases like PubMed and Scielo, focusing on malnutrition and infant mortality in Colombia. We used specific keywords and Boolean operators to identify relevant studies, emphasizing socio-economic, gender, and ethnic factors, while excluding non-peer-reviewed and outdated publications. Results: The relationship between gender and food/nutrition has deep historical and cultural roots. Patriarchal norms influence dietary habits based on gender roles, often placing undue responsibility on mothers for children's nutritional health, reflecting profound social intersections. Mortality due to malnutrition is most prevalent among indigenous and Afro-descendant children in rural, conflict-affected areas with limited access to healthcare. Unpaid domestic work restricts women's economic independence, intensifying challenges for single-parent households. Conclusion: A comprehensive understanding can shift institutional attitudes towards mothers, leading to more coherent policy strategies and effective interventions.